2022
DOI: 10.1039/d1cp05749a
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial thermal transport of graphene/β-Ga2O3 heterojunctions: a molecular dynamics study with a self-consistent interatomic potential

Abstract: The graphene/β-Ga2O3 heterojunction is widely used in high-power and high-frequency devices, of which the thermal management is vital to the device operation and life. Here we apply molecular dynamics simulation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Kang et al found that in the GRA-C 3 B vdW heterostructures, the conductance can be turned on or off according to the stacking order, which is the primary theoretical support for the design of switching devices based on GRA-C 3 B heterostructures [26]. Heat transfer and heat dissipation are the most severe and widespread matters to occur in micro and nanodevices [27], and the interfacial thermal transport between adjacent materials plays a vital role in the heat transfer process of devices [28]. In recent years, the thermal transport properties of some 2D heterostructures have been investigated, such as GRA-C 3 N [29], GRA-MoSe 2 [30], MoS 2 -MoSe 2 [31], GRA-h-BN [32], phosphorene-GRA [33] and so on.…”
Section: Introductionmentioning
confidence: 98%
“…Kang et al found that in the GRA-C 3 B vdW heterostructures, the conductance can be turned on or off according to the stacking order, which is the primary theoretical support for the design of switching devices based on GRA-C 3 B heterostructures [26]. Heat transfer and heat dissipation are the most severe and widespread matters to occur in micro and nanodevices [27], and the interfacial thermal transport between adjacent materials plays a vital role in the heat transfer process of devices [28]. In recent years, the thermal transport properties of some 2D heterostructures have been investigated, such as GRA-C 3 N [29], GRA-MoSe 2 [30], MoS 2 -MoSe 2 [31], GRA-h-BN [32], phosphorene-GRA [33] and so on.…”
Section: Introductionmentioning
confidence: 98%
“…25 It is particularly challenging to obtain an empirical potential that can accurately describe Ga 2 O 3 and diamond at the same time, such as the β-Ga 2 O 3 /diamond heterostructure. Although Xin et al have explored the interfacial heat transfer of graphene/β-Ga 2 O 3 based on its self-consistent interatomic potential, 26 whether it can be accurately applied to the interfacial heat transfer of β-Ga 2 O 3 /diamond remains to be verified. 27 Recent research efforts have been taken in the thermal transport investigation based on machine learning (ML).…”
Section: Introductionmentioning
confidence: 99%